The mechanisms of Pin1 as targets for cancer therapy - Liu, Chuanfeng; Dan, Lingying; Li, Quan; Bajinka, Ousman; Yuan, Xingxing (Frontiers in Immunology, 2024)
Targeted therapy has considerable promise for the effective eradication of cancer at the primary tumor site prior to subsequent metastasis. Using this therapeutic approach, gaining an understanding of mechanistic cancer models is essential for facilitating the inhibition or suppression of tumor growth. Among different oncogenes and proteins, the protein interacting with never-in-mitosis kinase-1 (Pin1) is particularly important. The interaction between Pin1 and phosphorylated threonine-proline motifs results in significant alterations in protein structure and function. In this review, we provide a comprehensive summary of the processes involving Pin1 and its mechanisms in the context of cancer therapy. Pin1 enhances signaling pathways in a number of different human cancers and plays a pivotal role in the suppressive mechanisms relevant to cancer treatment. It is essential for the regulation of proline-directed phosphorylation and for modulating tumor suppressors. Inhibitors of Pin1, particularly naturally occurring substances, have been found to inhibit the carcinogenic activity of Pin1, and consequently this protein could represent an excellent candidate for novel cancer treatment strategies, offering a valuable therapeutic target in carcinogenesis and treatment resistance.